If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying o = 5 + -1(2x + -17) Reorder the terms: o = 5 + -1(-17 + 2x) o = 5 + (-17 * -1 + 2x * -1) o = 5 + (17 + -2x) Combine like terms: 5 + 17 = 22 o = 22 + -2x Solving o = 22 + -2x Solving for variable 'o'. Move all terms containing o to the left, all other terms to the right. Simplifying o = 22 + -2x
| x+3.07+2.5=1.8 | | -80.2-9x=-21.9 | | 10a+55b= | | 3x+7-9x=-11 | | x+43=87 | | x+5=1.5x+2.5 | | 10f+2(5f+8)=-10f-4(2f-30) | | 5d+9=24 | | 2=17 | | 8ex=7 | | p*(q+r)=qp+pr | | y^2+9xy+18x^2=0 | | 32860-0.06x=x | | 7y+5=6y | | -43+11x=6x+32 | | -2k-16=3h-6 | | 2(x+4)=12x+62 | | 46=-6-8 | | 269.50=14 | | X-.4x=60 | | 20x+10y=0 | | 19-11n+16n-4= | | 9u^2+1u-10=0 | | X-x(.4)=60 | | 20x+10y=107 | | 3x+10=6x-19 | | 3z+1=34 | | -42-10x=53-5x | | 6x+9=4(-x) | | x^2(2x+3)+2x(3x^2+5x)= | | 24-2t-t^2=0 | | x^3+3x^2=4x-12 |